Direito de ser: formação e experiência na Educação de Jovens e Adultos - Medeiros, Mariana da Mota (2018)
The present research examined some aspects of the life and school stories of students from the Campo Limpo Youth and Adult Education Integrated Center (CIEJA), located in the outskirts of São Paulo – SP. The aim of this research was to investigate whether the experience in the youth and adult education has been helping in a human development that benefits the awareness towards the social condition and a resignification of the life stories of CIEJA’s students, providing conditions for the development of their sense of belonging, social identity and political formation. Therefore, based on the Critical Theory and on the concepts of prejudice, experience and political formation, the following procedures were carried out: literature and desk review of the youth and adult education in Brazil (EJA program); analysis of the political-pedagogical project of the CIEJA Campo Limpo; and questionnaires with open- and closed-ended questions answered by students from CIEJA Campo Limpo. It was possible to conclude that the structuring of an education project in the context of youth and adult education that makes possible the articulation of students’ experiences, their surroundings, and an integral education becomes fundamental for the creation of meaning for the school and for life itself. Thus, the CIEJA Campo Limpo has proven itself as an institutional and pedagogical reference in relation to the EJA program, since its scholar space is also a community, social and political area that integrates the diversity present in its surroundings, aspects that were verified in what students expressed in their answers in the questionnaires